Espai 13 : Comunicacions. El vigor de l'efimer. - Fundacio Joan Miro, Barcelona (Barcelona : Fundació Joan Miró, 1991)
Geismar, Jarg ; Rovira, Esther ; Saiz, Manuel ; Vacas, Paco ; Sanicne, Idroj ; Jasisnki, André
Espai 13 : Comunicacions. El vigor de l'efimer, Fundació Joan Miró, Barcelona, 3 octubre - 14 juny 1992
boek